2017
DOI: 10.1057/s41269-017-0063-z
|View full text |Cite
|
Sign up to set email alerts
|

Parliament in gross human rights violations: the case of Darfur

Abstract: Based on a study of three European parliaments, the article analyses parliamentary oversight on government policy towards gross human rights violations in third countries using the case of Darfur in Sudan (2003-2005). We find that parliaments with greater constitutional rights in foreign policy are more active in the scrutiny of executive action. Scrutiny is stronger in parliaments with developed and strong foreign affairs committees. Media and public awareness correlate with greater oversight activities in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…93 Pegan and Vermeulen found that in the context of foreign affairs committees, scrutiny was improved where there were 'developed and strong' committees. 94 The IPU's research has identified a number of risks for ineffective parliamentary committees including a weak mandate subject to political whims, lack of sufficient expertise, partisanship, compartmentalisation of human rights and reduced political influence where human rights are not prioritised by the parliament. 95 This last element is an important one, as even when a committee is effective in its own operations, it will need to have the ability to influence the parliament.…”
Section: How To Ensure Effective Mechanisms?mentioning
confidence: 99%
“…93 Pegan and Vermeulen found that in the context of foreign affairs committees, scrutiny was improved where there were 'developed and strong' committees. 94 The IPU's research has identified a number of risks for ineffective parliamentary committees including a weak mandate subject to political whims, lack of sufficient expertise, partisanship, compartmentalisation of human rights and reduced political influence where human rights are not prioritised by the parliament. 95 This last element is an important one, as even when a committee is effective in its own operations, it will need to have the ability to influence the parliament.…”
Section: How To Ensure Effective Mechanisms?mentioning
confidence: 99%